Immune Monitoring Assay for Extracorporeal Photopheresis Treatment Optimization After Heart Transplantation - Dieterlen, Maja-Theresa; Klaeske, Kristin; Bernhardt, Alexander A.; Borger, Michael A.; Klein, Sara; Garbade, Jens; Lehmann, Sven; Ayuk, Francis Ayuketang; Reichenspurner, Herrmann; Barten, Markus J. (Frontiers in Immunology, 2021)
Background: Extracorporeal photopheresis (ECP) induces immunological changes that lead to a reduced risk of transplant rejection. The aim of the present study was to determine optimum conditions for ECP treatment by analyzing a variety of tolerance-inducing immune cells to optimize the treatment. Methods: Ten ECP treatments were applied to each of 17 heart-transplant patients from month 3 to month 9 post-HTx. Blood samples were taken at baseline, three times during treatment, and four months after the last ECP treatment. The abundance of subsets of tolerance-inducing regulatory T cells (Tregs) and dendritic cells (DCs) in the samples was determined by flow cytometry. A multivariate statistical model describing the immunological status of rejection-free heart transplanted patients was used to visualize the patient-specific immunological improvement induced by ECP. Results: All BDCA+ DC subsets (BDCA1+ DCs: p < 0.01, BDCA2+ DCs: p < 0.01, BDCA3+ DCs: p < 0.01, BDCA4+ DCs: p < 0.01) as well as total Tregs (p < 0.01) and CD39+ Tregs (p < 0.01) increased during ECP treatment, while CD62L+ Tregs decreased (p < 0.01). The cell surface expression level of BDCA1 (p < 0.01) and BDCA4 (p < 0.01) on DCs as well as of CD120b (p < 0.01) on Tregs increased during the study period, while CD62L expression on Tregs decreased significantly (p = 0.04). The cell surface expression level of BDCA2 (p = 0.47) and BDCA3 (p = 0.22) on DCs as well as of CD39 (p = 0.14) and CD147 (p = 0.08) on Tregs remained constant during the study period. A cluster analysis showed that ECP treatment led to a sustained immunological improvement. Conclusions: We developed an immune monitoring assay for ECP treatment after heart transplantation by analyzing changes in tolerance-inducing immune cells. This assay allowed differentiation of patients who did and did not show immunological improvement. Based on these results, we propose classification criteria that may allow optimization of the duration of ECP treatment.